Serum Soluble Endoglin (sEng) as A Predictor of Preeclampsia Severity - Mustiqa Febriniata; Dian Ariningrum; Sienny Linawaty (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Preeclampsia is new-onset hypertension in pregnancy after 20 weeks of gestation. It is characterized by proteinuria or organ damage. Laboratory tests with high sensitivity and specificity in predicting severe preeclampsia are currently lacking due to the pathogenesis of preeclampsia which is still unclear. SEng (Soluble Endoglin), a glycoprotein expressed by syncytiotrophoblasts, is released into the maternal circulation in preeclampsia, acting as an anti-angiogenic through its binding to TGF-beta which then inhibits the vasodilation pathway. This angiogenic imbalance subsequently results in endothelial dysfunction and multiorgan damage. We investigated serum sEng as a predictor of severe preeclampsia by analyzing the risk factors of preeclampsia. An observational analytic study using a cross sectional design was conducted on pregnant women diagnosed with preeclampsia based on POGI (Perkumpulan Obstetri dan Ginekologi Indonesia) treated in Dr. Moewardi Hospital from June to July 2024. Serum samples of sEng were collected and examined using the sandwich ELISA method and then cut-off was determined. The multivariate multiple logistic regression with the backward stepwise method analysis obtained that sEng level with a cut-off point of 23.38 ng/mL could be used as an independent biomarker to predict severe preeclampsia, while other risk factors of preeclampsia including maternal age, obesity, parity, history of preeclampsia, and gestational age could not predict the severity of preeclampsia (p <0.05). Further study is needed with a larger sample size involving multiple centers to generalize the outcomes and top analyze other preeclampsia risk factors.